Oyster-Based Amplang from Lajari, Barru Regency - Achmad Rizal; Muhammad Anas; Lily Dianafitri Hasan (Politeknik Pariwisata Makassar, 2024)
This research aims to find out how to make oyster-based amplang taken directly in Lajari, Barru Regency. The abundance of marine natural resources, without oyster cultivation, can breed naturally, so that there is a culinary tour of grilled oysters in Lajari, Barru Regency. The very little utilization of oysters that are only grilled makes this research utilize oysters as a substitute for the main ingredient in making amplang, Oysters were chosen as a substitute for fish in making amplang in the hope of providing product variations and increasing the added value of local marine products. This research used an experimental approach. Data was collected through observation and documentation of the amplang making process as well as organoleptic tests to assess the quality of the final product. The results showed that the use of oysters as the main ingredient in making amplang resulted in a product with unique texture and flavor but less than optimal. In addition, this study also emphasized the importance of maintaining consistency in the manufacturing method to ensure optimal product quality. Thus, this research contributes to the diversification of marine resource-based culinary products in Barru Regency and opens up new opportunities for the development of the local food industry. It is hoped that the results of this study can encourage further innovation in the utilization of oysters and support the economic development of the community.